2011
DOI: 10.5194/acp-11-6337-2011
|View full text |Cite
|
Sign up to set email alerts
|

<i>α</i>-Pinene nitrates: synthesis, yields and atmospheric chemistry

Abstract: Abstract. The biogenic volatile organic compound α-pinene is one of the dominant monoterpenes emitted to the Earth's atmosphere at an estimated rate of ∼50 Tg C yr −1 . Its atmospheric oxidation products in the presence of NO can lead to ozone production, as well as production of secondary organic aerosol (SOA). The major oxidation pathway of α-pinene is reaction with OH, which in the presence of NO can form either α-pinene nitrates or convert NO to NO 2 , which can photolyze to form ozone. In this work, we su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…S1 ), indicate that a substantial fraction of the NO x originated from soil 27 in the forest rather than from anthropogenic sources, to form aerosol nitrate. Nitrate radicals in the atmosphere are known to have a high reactivity to α-pinene and can subsequently form α-pinene nitrates 39 . Recently, chamber experimental and modelling studies have shown that the addition of nitrate functional groups inhibit CCN activation by reducing its miscibility with water 40 , 41 , which also supports the observed reduction in CCN activity for particles in the vicinity of a biogenic source area.…”
Section: Resultsmentioning
confidence: 99%
“…S1 ), indicate that a substantial fraction of the NO x originated from soil 27 in the forest rather than from anthropogenic sources, to form aerosol nitrate. Nitrate radicals in the atmosphere are known to have a high reactivity to α-pinene and can subsequently form α-pinene nitrates 39 . Recently, chamber experimental and modelling studies have shown that the addition of nitrate functional groups inhibit CCN activation by reducing its miscibility with water 40 , 41 , which also supports the observed reduction in CCN activity for particles in the vicinity of a biogenic source area.…”
Section: Resultsmentioning
confidence: 99%
“…In pristine atmosphere, the effective rate of RO 2 with NO/HO 2 /R′O 2 could be very low, e.g., at ∼0.025 s –1 with 100 pptv (∼2.5 × 10 9 molecules cm –3 ) of NO/HO 2 /R′O 2 altogether, allowing the possibility for unimolecular isomerizations in RO 2 radicals. It is difficult to estimate the RONO 2 yields; e.g., molar yields of α-pinene nitrates ranged from 0.13 ± 0.035 to 0.26 ± 0.07. , For the time being, a yield of ∼0.20 at 298 K is assumed by referring to the values in α-pinene and other RO 2 radicals of similar sizes. Yields of RONO 2 would be higher at lower temperatures.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Atmospheric ON formation occurs by either OH radical-initiated photochemical reactions or NO 3 radical-initiated nocturnal reactions of anthropogenic and biogenic volatile organic compounds. These reactions can produce ON compounds with vapor pressures low enough to condense and form SOA. In one such study, the formation of a series of ON compounds from reactions of α-pinene with NO 3 radicals was observed . In another study, the photochemistry of the hydroxyl radical oxidation of α-pinene under high NO x conditions was studied and the formation of a range of ON compounds from α-pinene in the presence of nitric oxide (NO) was reported .…”
Section: Introductionmentioning
confidence: 99%